Prevalence of Medical Student Syndrome among Medical Students of Nepal - Nepal, Samata; Atreya, Alok; Bhandari, Swasti; Sapkota, Laxmi Prasad; Menezes, Ritesh G.; Gnawali, Laxman; Adhikari, Kishor (Journal of Nepal Health Research Council, 2024)
Background: Medical student syndrome (MSS) entails the development of symptoms of the same disease as the one being studied in medical students. This study aimed to determine the prevalence of Medical student syndrome among medical students in Nepal and identify associated factors. Methods: A Cross-sectional study was conducted at Lumbini Medical College Palpa, Nepal on medical students. Google form-based questionnaire was made, and the link was distributed to the students. A cut-off score was derived for Medical student syndrome. Students whose scores exceeded this threshold were categorized as having experienced Medical student syndrome. The responses received from the consenting students were downloaded in a Microsoft Excel spreadsheet and exported to SPSS v 26 and analysed. Results: The overall prevalence of Medical student syndrome was 17.8%. There was no significant difference in Medical student syndrome scores between genders (p = 0.801). However, year of study significantly influenced Medical student syndrome scores (p = 0.001, η² = 0.069), with final year students reporting higher scores. Conclusions: This cross-sectional study revealed a significant prevalence of Medical Student Syndrome among medical students in Nepal, with nearly 18% reporting symptoms of the condition. Keywords: Hypochondriasis; medical students; mental health; Nepal.